Electrochemical and analytical study of electroplating additive in copper plating solution for microvia filling. Issue 3 (5th August 2019) - Tao, Zhihua; Liu, Guanting; Li, Yuanxun; Su, Hua
Abstract : Purpose: The adsorption and acceleration behavior of 3-mercaptopropyl sulfonate (MPS) were investigated by electrochemical tests for microvia filling by copper electroplating. Design/methodology/approach: The synergistic effects of one suppressor of propylene oxide ethylene oxide propylene oxide named PEP and MPS as the accelerator during copper electroplating were also investigated by electrochemical methods such as electrochemical impedance spectroscopy cyclic voltammetric stripping (CVS) and Galvanostatic measurements (GMs). Findings: The research results suggest that the adsorption of MPS onto the Cu-RDE metal surface was a spontaneous process and the adsorbing of MPS on cathode was proposed to physical-chemistry adsorption in the plating formula. There was no potential difference (i.e. ?? = 0) of GMs until MPS was injected into the plating solution suggest that copper deposition is not diffusion-controlled in the presence of PEP–Cl–JGB. Originality/value: A new composition of plating bath was found to be effective to perform bottom-up copper filling of microvias in the fabrication of PCB in electronic industries. The adsorption of MPS into the Cu-RDE metal surface was a spontaneous process and the adsorbing of MPS on cathode was studied by EIS and the results proposed to physical-chemistry adsorption in the plating formula. An optimal plating solution composed of CuSO4, H2SO4, chloride ions, PEP, MPS and JGB was obtained, and the microvia could be fully filled using the plating formula.